Environmental security - a key to sustainable economic and environmental development of Ukraine - Koshkalda Iryna; Dombrovska Olena; Chebanova Yuliia; Skyba Viktoriia; Скиба, Вікторія Павлівна; Ayubova Elnara; Аюбова, Ельнара Мусаібовна (Nemoros s.r.o. Prague, 2021)
The monograph is prepared in the framework of research topics: «Management of national security in the context of globalization challenges: macro, micro, regional and sectoral levels» (state registration number 0118U005209, Poltava State Agrarian Academy, Ukraine), «The concept of investment and financial and credit support of technical and technological renewal and development of agricultural production as a component of food and economic security» (state registration number 0120U105469, Poltava State Agrarian Academy, Ukraine), «Macroeconomic planning and management of the higher education system of Ukraine: philosophy and methodology» (state registration number 0117U002531, Institute of education content modernization of the Ministry of Education and Science of Ukraine, Ukraine), «Infocommunication aspects of economic security» (Protocol 1-21 of February 25, 2021, Information Systems Management University, Latvia).Any partial or entire reproduction, of this document should cite the source. Materials are printed in original languages. The authors are responsible for the statement, the content and reliability of the materials.
Keywords: Environmental security; sustainable economic; environmental development